2022
DOI: 10.1002/srin.202200236
|View full text |Cite
|
Sign up to set email alerts
|

Study on Surface Modification of Fe–Si–Cr Alloy by Selective Oxidation Heat Treatment and its Corrosion Properties

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/srin.202200236.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Zhang et al [ 21 ] reported that for Fe–10Cr–1.2Si (wt%) steel, a sufficient amount of Si could provide nucleation sites for the original Cr 2 O 3 to decrease the grain size. Park et al [ 22 ] reported that Fe–3Si–5.5Cr (wt%) steel has inner and outer oxide layers with SiO 2 and Cr 2 O 3 , which improves its oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 21 ] reported that for Fe–10Cr–1.2Si (wt%) steel, a sufficient amount of Si could provide nucleation sites for the original Cr 2 O 3 to decrease the grain size. Park et al [ 22 ] reported that Fe–3Si–5.5Cr (wt%) steel has inner and outer oxide layers with SiO 2 and Cr 2 O 3 , which improves its oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…), Cr [9][10][11] and Si [12] significantly improve the oxidation resistance of steel. Jae-Young Park et al [13] found that the oxidation of Fe-Si-Cr alloys at 650 • C produced a double-layer structure oxide with Cr 2 O 3 in the outer layer and SiO 2 in the inner layer. Tianyuan Wang et al [14] found that Si makes the oxide layer flat and reduces spalling, which improves the antioxidant performance at 800 • C more than five times.…”
Section: Introductionmentioning
confidence: 99%